IPTEKS FAKTOR – FAKTOR PENGHAMBAT PROSES E-REGISTRATION DI KANTOR PELAYANAN PAJAK PRATAMA MANADO - Manderos, Julycia Verent; Suwetja, I Gede (Universitas Sam Ratulangi, 2018)
The Directorate General of Taxation currently utilizes internet technology to improve service, one of which is by conducting an online registration of NPWP or e-Registration so that new taxpayers are easier to register anywhere and anytime. But in this case there are things that hinder the process. Based on the research there are several factors that hinder the e-Registration process, such as: (1) Data received by the Extensification Section is incomplete, (2) The internet network are often disrupted, (3) The lack of public attention to the socialization that has been carried out. The author suggests for KPP Pratama Manado to re-socializing about e-Registration, improving the quality of the socialization and improving the internet network.Keyword : E-Registration, NPWP, Taxpayers, Socialization, Public Attention, Internet Network